Bandgap enhancement of periodic nonuniform metamaterial beams with inertial amplification mechanisms. (14th January 2020) - Muhammad, Shoaib; Wang, Shuai; Li, Fengming; Zhang, Chuanzeng
The aim of this study was to obtain bandgaps that are much better, that is at lower frequencies and in broader frequency ranges. Novel nonuniform metamaterial beams with periodically variable cross sections and inertial amplification mechanisms are designed and investigated by numerical and experimental methods. Flexural vibration equations of the nonuniform metamaterial beams are established, and the enhanced bandgap and vibration reduction properties are achieved by combining Bragg scattering and the inertial amplification mechanisms. Numerical results of the bandgaps for the periodic elastic beams with and without the inertial amplification mechanisms are validated by comparing them with the results of vibration experiments. Effects of the amplification mass and angle on the bandgap properties are investigated. Larger amplification mass and angle lead to much enhanced bandgap performances of the nonuniform metamaterial beams in lower to higher frequency ranges.